A Phage Receptor-Binding Protein as a Promising Tool for the Detection of Escherichia coli in Human Specimens - Costa, Susana P.; Cunha, Alexandra P.; Freitas, Paulo P.; Carvalho, Carla M. (Frontiers in Microbiology, 2022)
Escherichia coli is a problematic pathogen that causes life-threatening diseases, being a frequent causative agent of several nosocomial infections such as urinary tract and bloodstream infections. Proper and rapid bacterial identification is critical for allowing prompt and targeted antimicrobial therapy. (Bacterio)phage receptor binding proteins (RBPs) display high specificity to bacterial surface epitopes, therefore, are particularly attractive as biorecognition elements, potentially conferring high sensitivity and specificity in bacterial detection. In this study, we elucidate for the first time the potential of a recombinant RBP (Gp17) to recognize E. coli at different viability states, such as the viable but not culturable cells, which are not detected by conventional techniques. Moreover, by using a diagnostic method in which we combined magnetic and spectrofluorometric approaches, we demonstrated the ability of Gp17 to specifically detect E. coli in various human specimens (e.g., whole blood, feces, urine, and saliva) in about 1.5 hours, without requiring complex sample processing.